The design of an individualized cylindrical vaginal applicator with oblique guide holes using 3D modeling and printing technologies - Zhao, Zhipeng; Tang, Xiaodi; Mao, Zhuang; Zhao, Hongfu (Journal of Contemporary Brachytherapy, 2019)
High-dose-rate brachytherapy for cervical cancer after subtotal hysterectomy using standardized applicators cannot achieve a good absorbed-dose coverage of the target volume in special tumor morphologies and topographies due to the steep dose gradient. The aim of this pictorial essay is to present an individualized cylindrical vaginal applicator with oblique guide holes using 3D modeling and printing technologies used at the China-Japan Union Hospital of Jilin University for cervical cancer patients. We use images to describe the steps of this method.